Hydroformylation of 1-octene using rhodium–phosphite catalyst in a thermomorphic solvent system - Shaharun, Maizatul Shima (2010)
The use of a liquid-liquid biphasic thermomorphic or temperature dependent multicomponent solvent (TMS) process, in which the catalyst remains as a residue in one of the liquid phases and the product goes preferably to the other liquid phase, can be an enabling strategy of commercial application of hydroformylation processes with high selectivity, efficiency and ease of product separation and catalyst recovery. This paper describes the synthesis of n-nonanal, a commercially important fine chemical, by the hydroformylation reaction of 1-octene using a homogeneous catalyst consisting of HRh(PPh3)3(CO) and P(OPh)3 in a TMS- system containing propylene carbonate (PC), dodecane and 1,4-dioxane. At a reaction temperature of 90ºC and syngas pressure of 1.5 MPa and 0.68 mM HRh(CO)(PPh3)3, the conversion of 1-octene and the yield of total aldehyde were 97 % and 95 %, respectively. With a reaction-time of 2 h and a selectivity of 89.3 %, this catalytic system can be considered as highly reactive and selective. The resulting total turnover number was 600 while the turnover frequency was 400 h-1. The effect of concentration of 1-octene, catalyst loading, partial pressure of CO and H2 and temperature on the rate of reaction has been studied at temperature of 353, 363 and 373 K. The rate was found to be first order with respect to catalyst, 1-octene and partial pressure of H2. The rate vs. PCO shows a typical case of substrate inhibited kinetics. The kinetic behavior differs significantly from the kinetics of conventional systems employing HRh(CO)(PPh3)3 in organic solvents. Most notable are the lack of olefin inhibition, and the absence of a critical catalyst concentration. The altered behavior relative to conventional systems may be due to the solvent effects and the presence of the excess phosphite ligand. An empirical rate equation has been proposed and kinetic parameters evaluated. The activation energy was found to be 69.8 kJmol-1. The work done so far establishes the potential of the thermomorphic solvent system and the rhodium phosphite complex catalyst for the hydroformylation of 1-octene.